Intestinal dysbiosis in autoimmune diabetes is correlated with poor glycemic control and increased interleukin-6: A pilot study - Higuchi, Bruna Stevanato; Rodrigues, Nathália; Gonzaga, Marina Ignácio; Paiolo, João Carlos Cicogna; Stefanutto, Nadine; Omori, Wellington Pine [UNESP]; Pinheiro, Daniel Guariz [UNESP]; Brisotti, João Luiz; Matheucci, Euclides; Mariano, Vânia Sammartino; de Oliveira, Gislane Lelis Vilela [UNESP] (Frontiers, 2018)
Intestinal dysbiosis associated with immunological deregulation, leaky gut, bacterial translocation, and systemic inflammation has been associated with autoimmune diseases, such as type 1 diabetes (T1D). The aim of this study was to investigate the intestinal dysbiosis in T1D patients and correlate these results with clinical parameters and cytokines. The present study was approved by the Barretos Cancer Hospital (Process number 903/2014), and all participants have signed the informed consent in accordance with the Declaration of Helsinki, and answered a questionnaire about dietary habits. Stool samples were used for bacterial 16S sequencing by MiSeq Illumina platform. IL-2, IL-4, IL-6, IL-10, IL-17A, TNF, and IFN-γ plasma concentrations were determined by cytometric bead arrays. The Pearson's chi-square, Mann-Whitney and Spearman correlation were used for statistical analyses. Alpha and beta diversities were conducted by using an annotated observed taxonomic units table. This study included 20 patients and 28 controls, and we found significant differences (P < 0.05) among consumption of vegetables, proteins, milk and derivatives, spicy food, and canned food when we compare patients and controls. We detected intestinal dysbiosis in T1D patients when we performed the beta diversity analysis (P = 0.01). The prevalent species found in patients' stool were the Gram-negatives Bacteroides vulgatus, Bacteroides rodentium, Prevotella copri, and Bacteroides xylanisolvens. The inflammatory interleukin-6 was significantly increased (P = 0.017) in patients' plasma. Furthermore, we showed correlation among patients with poor glycemic control, represented by high levels of HbA1C percentages and Bacteroidetes, Lactobacillales, and Bacteroides dorei relative abundances. We concluded that there are different gut microbiota profiles between T1D patients and healthy controls. The prevalent Gram-negative species in T1D patients could be involved in the leaky gut, bacterial translocation, and poor glycemic control. However, additional studies, with larger cohorts, are required to determine a signature of the intestinal microbiota in T1D patients in the Brazilian population.
Keywords: Dietary habits; Glycemic control; Inflammatory cytokines; Interleukin-6; Intestinal dysbiosis; Type 1 diabetes